Assessment of biosilica nanoparticles from rice husk for fabrication of colloidosomes in advanced drug delivery - Sunday M. Ajayi; Samuel O. Olusanya; Sunday F. Abimbade; Abiodun Aladetuyi; Oluwabamise L. Faboya; Emmanuel G. Olumayede; Cecilia O. Akintayo; Dosu Malomo; Oluwaseyi R. Ogede (Next Nanotechnology)
The study of colloidosomes is rapidly expanding due to their potential as drug carriers and their capacity for tailoring active ingredient delivery to specific biological targets. While synthetic particles like cadmium selenide, polystyrene, synthetic silica, and zinc oxide are commonly used for colloidosome preparation, they are not eco-friendly and can be harmful if their permitted concentration is exceeded. This review assesses the physicochemical properties of biosilica nanoparticles derived from rice husks as a potential material for colloidosome fabrication, focusing on their potential as advanced drug delivery vehicles. Biosilica nanoparticles (BSiO2-NPs) have gained significant attention from researchers due to their biomedical properties such as porosity, biocompatibility, large specific surface area, biodegradability, and shape. It has surface area 110–1000 m3/g, pore volume 0.4 – 1.5 cm3/g and pore diameter 2 – 15 nm. Other physicochemical properties of amorphous biosilica are whiteness index (93.24–96.66), water content (0.49–2.81 %), density (0.56–0.95 g /ml) and antifungal properties. A mesoporous biosilica nanoparticles from rice husk have a spherical shape, highly ordered hexagonal structure, large specific surface area (>973 m2/g), high pore volume (>0.87 cm3/g), and pore diameter (>2.7 nm), which make it a potential material for colloidosome fabrication. Therefore, preparation, structural characterization, loading factors, and merits of biosilica nanoparticles in colloidosome fabrication for drug delivery are discussed, as well as their health risk assessment, benefits, and prospects. The study also highlights that the resulting colloidosome microcapsules and their resistance to harsh conditions are influenced by factors like particle’s porosity, shape, surface chemistry, and surface-area-to-volume ratio, which are characteristic of biosilica nanoparticles derived from rice husks.